PERBANDINGAN NILAI KEKERASAN DAN STRUKTUR MIKRO MATERIAL PISTON SEPEDA MOTOR 4 TAK ORIGINAL DAN IMITASI - Nofri, Media (Bina Teknika, 2019)
The function of the piston is to accept the pressure from the combustion of the gas mixture and continue the pressure to pass through the connecting rod. The use of aluminum as a piston material is inseparable from its properties and is very suitable for pistons. n this study three piston materials were tested, namely piston A (Original), B (Imitation 1) and C (Imitation 2) with Aluminum material which also contained Silicon (AlSi). The tests carried out included testing the chemical composition, microstructure photographed from various position and hardness by the Vickers method.  The results of these tests obtained varying hardness values with an average piston A value of 129 HV, piston B an average of 148.2 HV, piston C an average of 135.2 HV. The results of the microstructure test on piston C have srinkage casting defects and porosity defects while piston A and B have no defects. Whereas in testing the chemical composition of the value contained in the piston piston A has Al 81.7% and Si 14.0%, piston B Al 82.2% and Si 14.3%, piston C Al 83.5% and The 13.2%. From the results of the chemical composition test, the hardness value and microstructure of the three materials can be said to have almost the same value